Effects of Social Participation by Middle-Aged and Elderly Residents on the Utilization of Medical Services: Evidence From China - Liu, Tai-Yi; Qiu, De-Chao; Chen, Ting (Frontiers in Public Health, 2022)
Abstract Objectives: Aim to evaluate the effect of social participation on utilisation of medical services among middle-aged and elderly residents in China. Methods: We used data from the 2018 wave of the China Health and Retirement Longitudinal Study. Social participation is classified into three types. Furthermore, to control for confounding factors, our study computed propensity score matching (PSM) to evaluate the effect of social participation on the utilisation of medical services. Result: The result of PSM indicates that social participation significantly positively affects the utilisation of outpatient services, the average treatment effect on the treated (ATT = 0.038***) and the utilisation of inpatient services (ATT = 0.015**) by middle-aged and elderly residents. Furthermore, the utilisation of outpatient health care services was significantly positively associated with leisure activities (ATT = 0.035***), social activities to help others (ATT = 0.031***), and learning activities to gain new knowledge (ATT = 0.034***) among middle-aged and elderly residents. The utilisation of inpatient health care was significantly positively associated with leisure activities (ATT = 0.015***) but had no significant association with social deeds that help others and increased new knowledge among middle-aged and elderly residents. Conclusion: Thus, social participation significantly positively affects healthcare utilisation by middle-aged and elderly residents. Hence, the government and society should provide more conveniences and promote social participation among middle-aged and elderly residents.